SOSIALISASI KESADARAN BENCANA ALAM TANAH LONGSOR DI DESA PANDAN LANDUNG KABUPATEN MALANG - Dwi Kurniawati; Yuli Ifana Sari (LPPM IKIP Jember, 2018)
Land condition in Pandan Landung village is not flat (increasing upward its height) and tend to wavy with clay texture condition and loose soil. The increasing number of land conversion to be used as housing and agriculture causes Pandan Landung Village to potentially landslide disaster in case of heavy rain. Although a slope is vulnerable or potentially landslide, the slope will not yet be avalanched or subject to stability without being triggered by the triggering process. The triggering process such as high rainfall, the number of settlements built on the slopes, or slopes that are only planted with roots that are not able to withstand the flow of the surface due to rain. The socialization materials were prepared based on the analysis of participants' needs that were implemented through socialization and assistance with community involvement. The series of socialization activities are: Information and frequently asked questions about the understanding of natural disaster landslide, the type of landslide, the cause, and its impact. The results obtained from the activities of devotion include: 1) Socialization materials can be delivered properly .. 2) Response participants socialization landslide disaster is very good. 3) In the question and answer session there are several questions asked by the participants. And 4) The ability of socialization participants in mastering the landslide disaster material and their mitigation efforts is still lacking, but at least there is an increase of knowledge